(untitled) (International relations and international law Journal, 2018)
The willingness of RK integration into the world educational community, to acknowledgment of our diplomas and our specialists in the countries of the civilized world make us analyze the US system of higher education, reveal its peculiarities and pay attention to its positive sides. We should not simply fix their positive tendencies in the practical work at the universities of RK. All mentioned above testify the availability of contradiction of the need of RK to the world modern tendencies and real situation of this problem in the country. The given contradiction has determined the theme of my research: what are the tendencies and peculiarities of the development of the higher education of the USA. So, the subject of my research is the perfection of training and upbringing of the future specialists in the modern higher institutions of RK with the help of combined US experience. The maximum success in modernization of the higher educational system in RK can be achieved in case all program directions of the Government placed into educational policy take all the best possible from positive potential of the US higher educational system in main directions: qualitative selection of school-leavers, qualitative teaching staff, high level of organizing of teaching process, finance provision, development of the infrastructure of the university. The analysis and study of literature on the given problem have revealed that in the Republic Kazakhstan different aspects of comparative pedagogics, methods of comparative and pedagogical researches, educational policy of the higher education are regarded in various works and researches. Alongside with it the problem of the quality of the educational system of RK, tendencies of its reforming, the issues of globalization and integration, the development of the national model of the higher education are also considered in various scientific works. The detailed and full analysis in carried out in these works. The authors outline their vision of the national model of the education in RK which should take all the best from world experience adding local cultural and educational peculiarities. But in all scientific works the problems and importance of launching of advanced practice and traditions of the western universities into local pedagogical practice have not been solved. Key words: modernization of the higher educational system, important tendencies, world educational market, the process of restructuring, global priorities, integration into the global educational environment, reforming the national education system